Las izquierdas y derechas de Uruguay, Brasil y Chile ante el peronismo (1943-1955) - Ernesto Bohoslavsky (Nuevo mundo - Mundos Nuevos, 2020)
This essay focuses in the manners that Uruguay, Brazil and Chile political forces assessed the rising Peronist movement in the forties and later the Peronist government. In the three countries anti-Peronism became a significant element of the political life and anti-Peronist discourses and interpretations crafted in Argentina were frequently used by leftist and right-wing politicians. Opposite to them, union leaders and politicians in the above mentioned countries showed sympathy toward Peron and his policies. Peronist government fueled this interest with covert funding and by supplying propaganda to running candidates as Getúlio Vargas or Carlos Ibáñez del Campo. This article shows that the ideological left-wing dyad in these countries cases was overlapped with pro-Peronist/anti-Peronist opposing identities, as it has occurred in Argentina since the mid-forties.